Keefektifan Mind Mapping Tony Buzan Berbantuan Media Play While Thinking Terhadap Motivasi Dan Kreativitas Siswa - Anggraeni Anggraeni; Kartika Yuni (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine the effectiveness of the mind mapping learning model assisted with play while thinking on students' motivation and creativity. The problems faced are low student motivation and teachers do not pay attention to student creativity in learning. This type of research is true-experimental design with pretest-posttest control group design. Random sampling technique. Data analysis techniques used normality test, homogeneity test, paired sample test, t test and simple linear regression test. The results of the research show: (1) There is an effect of using mind mapping assisted with play while thinking on student motivation and creativity, the results of regression test show a significance level of 0.003> 0.005, (2) There are differences in the use of mind mapping assisted play while thinking on motivation and creativity students, the results of the t test with a significance level of 0.000 <0.05, and (3) the mind mapping learning model assisted with play while thinking is effective in increasing student motivation and creativity, the results of the paired sample t-test with a significance level of 0.000> 0.05.